2008
DOI: 10.1007/s10815-007-9192-z
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of ureaplasma urealyticum, mycoplasma hominis, chlamydia trachomatis and neisseria gonorrhoeae infections, and the rubella status of patients undergoing an initial infertility evaluation

Abstract: Purpose To determine the prevalence of positive test for Ureaplasma urealyticum (UU), Mycoplasma hominis (MH), Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG) infections, and their corresponding Rubella status when undergoing workup for infertility. Methods Retrospective chart review to determine infection status for UU, MH, CT, and NG as determined by cervical swab, as well as the serum Rubella antibody titer. Results A total of 46 patients of the patients reviewed were positive for UU (20.1%), three p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 18 publications
(14 reference statements)
4
9
1
4
Order By: Relevance
“…In the Unites States, the prevalence of infection with M. hominis was 1.3% and in Poland (determined by biochemical method) was 3.7% indicating that the prevalence of infection was lower as compared with Iran regarding to the present study (24,25). Najar Peerayeh et al (23) and Vatani (5) showed that prevalence of Mycoplasma in infertile women was 16% and 13.3 % respectively, indicating higher prevalence as compared with the present study.…”
Section: Discussioncontrasting
confidence: 45%
“…In the Unites States, the prevalence of infection with M. hominis was 1.3% and in Poland (determined by biochemical method) was 3.7% indicating that the prevalence of infection was lower as compared with Iran regarding to the present study (24,25). Najar Peerayeh et al (23) and Vatani (5) showed that prevalence of Mycoplasma in infertile women was 16% and 13.3 % respectively, indicating higher prevalence as compared with the present study.…”
Section: Discussioncontrasting
confidence: 45%
“…Nel nostro studio i batteri più comunemente rilevati in tutte le popolazioni prese in esame sono gli Ureaplasma, con U. parvum che raggiunge il range di positività più alto, in accordo con i lavori presenti in letteratura (21,34,36). Stessa concordanza con la letteratura (range di positività: 1.3%-21.9%) si trova per la positività di M. hominis che è del 10.37% nei tamponi cervicali (5,21,34,36); negli uomini (tampone uretrale e liquido seminale) M. hominis si ritrova rispettivamente nel 5.6% ed 8%, con una positività leggermente superiore rispetto a quella riportata in letteratura (39,43). Anche la positività a M. genitalium, che è del 1.75%, è in accordo con quanto riportato in letteratura (5,34,36,39,43).…”
Section: Discussioneunclassified
“…Es por ello que algunas investigaciones no recomiendan, durante la evaluación inicial de las parejas infértiles, la detección rutinaria de los mycoplasmas (UU y MH) sin ninguna evidencia clínica, dado a que no es rentable debido a bajas tasas de detección (23,36,44). No obstante, la infección por este microorganismo puede reducir la tasa de éxito de los tratamientos de infertilidad altamente especializados, entre ellos la inseminación artificial intrauterina, la transferencia de gametos, la fertilización in vitro o la inyección intracitoplasmática de espermatozoides; asimismo, podría causar una marcada reducción del desarrollo embrionario temprano posterior a la fertilización in vitro (22).…”
Section: Discussionunclassified
“…Si bien el papel exacto de UU en pacientes con problemas de infertilidad no se ha dilucidado completamente y no está claro si contribuye significativamente a la infertilidad (22). Teniendo en cuenta que la infección por UU a menudo es concomitante con CT, la cual está relacionada con infertilidad debido a factor tubárico, la presencia de UU pudiese tener un papel en la infección subclínica y tuboperitoneal, por lo que se debe ofrecer el cribado de estas infecciones en las pacientes sometidas a una evaluación de infertilidad (23).…”
Section: Introductionunclassified